Model for Evaluating CO2 Emissions and the Projection of the Transport Sector - Daniel Ospina; Sebastian Zapata; Mónica Castañeda; Isaac Dyner; Andres Julian Aristizabal; Nicolas Escalante (International Journal of Electrical and Computer Engineering (IJECE), 2018)
This article presents a system dynamics model to analyze the growth of cars and the effect of different policies on carbon emissions from the transport sector. The simulation model used in this work was built using the methodology of systems dynamics (SD) developed by Jay W. Forrester at the Massachusetts Institute of Technology (MIT). The model was applied to the transport sector of the city of Bogota, Colombia for a period of time between 2005 and 2050. The information used to feed the model comes from reliable sources such as DANE (National Administrative Department of Statistics) and EIA (U.S Energy Information Administration). Four scenarios were proposed that relate urban development policy and environmental policy. The main results indicate that the number of cars in Bogota can reach up to 13 million vehicles in 2050 and the projection of CO2 emissions would reach 34 million TonCO2 in the absence of an appropriate environmental policy.